Early Abusive Relationships–Influence of Different Maltreatment Types on Postpartum Psychopathology and Mother-Infant Bonding in a Clinical Sample - Frohberg, Julia; Bittner, Antje; Steudte-Schmiedgen, Susann; Junge-Hoffmeister, Juliane; Garthus-Niegel, Susan; Weidner, Kerstin (Frontiers in Psychiatry, 2022)
Postpartum psychopathology is a well-documented risk factor for impaired mother-infant bonding and thus child development. Increasingly, the focus of research in this area lies on maternal adverse childhood experiences that mothers bring into the relationship with their own baby, especially regarding the possible intergenerational transmission of traumatic experiences. Several studies showed that there is no direct link between child maltreatment and mother-infant bonding as one part of mother-child relationship, but that this link is mediated by postpartum psychopathology. To date, few studies examined differential effects between sexual, physical, and emotional abuse, and physical and emotional neglect, especially in a clinical sample. The aim of this study is to investigate whether the relationship between child maltreatment, psychopathology, and mother-infant bonding can be found for different forms of child maltreatment in patients of a mother-baby unit. Our sample consisted of 330 mothers of a mother-baby-unit in a psychosomatic clinic, who filled out self-report measures at time of admission. Mothers reported on maternal child maltreatment history with the Childhood Trauma Questionnaire, on current psychopathology with the Brief Symptom Inventory, and on mother-infant bonding with the Postpartum Bonding Questionnaire. Mediation analyses were performed with psychopathology as mediator, child maltreatment history as independent, and mother-infant bonding as dependent variable. There was no total effect of child maltreatment on mother-infant bonding. However, there were significant indirect effects of child maltreatment in general and of the various forms of child maltreatment on mother-infant bonding via psychopathology. The strongest effect was found for emotional abuse. After controlling for psychopathology, the direct effect of physical abuse on mother-infant bonding presented as a negative significant effect. This indicates that the more severe the physical abuse experienced, the better the self-reported bonding. A similar, but non-significant trend was found for sexual abuse. Our findings highlight the importance of assessing neglect forms of child maltreatment as well as abuse in women during the perinatal period. It further supports initial findings that different forms of child maltreatment can have differential effects on mother-infant bonding as one aspect of the mother-child relationship. Further research should include observational data to compare with self-report measures.